Structural equation model: Organizational performance among state universities and colleges in Philippines - Jomarie V. Baron; Ava Clare Marie O. Robles (Goodwood Publishing, 2023)
Purpose: This study identifies the best model fit for organizational performance among state universities and colleges (SUCs) in Region XII, Philippines, influenced by innovation strategy and quality management practices. Research methodology: The study design was descriptive-correlative. Since the design is descriptive, it provides a comprehensive explanation of organizational performance among SUCs in Region XII. Furthermore, the Mean and latent variable analysis (LAVAAN) using the r-studio package were the statistical measures employed to evaluate the hypothesis. Results: The findings indicate that SUCs effectively fulfill their instructional, research, and extension functions, and their organizational performance is influenced by both innovation strategies and quality management practices. The developed model revealed a positive relationship between technological innovation, continuous improvement practices, and organizational performance. However, a negative relationship was observed between management innovation and support. Limitations: This study was limited to SUCs in Region XII. The variables for organizational performance were limited to performance in instruction, research, and extension, while predictors of these performances revolved only in innovation strategy and quality management. Contribution: The intended implementation of the model among SUCs aims to enhance their performance and align it with the mandates of the Commission on Higher Education (CHED). Overall, this study's output will contribute to the pool of knowledge, particularly in the field of educational management. Novelty: The study not only provides a comprehensive understanding of organizational performance among SUCs but also develops a model that best fits organizational performance, which has not been done in previous studies.